Effectiveness Of Posyandu Cadres Towards The Stimulation Program Detection And Intervention Early To Grow Flowers (SDIDTK) Baduta In Jambi City In 2024 - Roza Rizana; Rumita Ena Sari; Dwi Noerjoedianto (Jurnal EduHealth, 2024)
Background: Stimulation of Early Growth and Development Detection and Intervention (SDIDTK) is an effort to monitor and screen children's physical, mental and emotional development to detect growth disorders and prevent ongoing disorders during the toddler years. The aim of this research is to evaluate the effectiveness of Posyandu cadres in implementing the SDIDTK Program in Jambi City in 2024. Method: This research uses a quantitative approach with a cross-sectional design. The population consists of all SDIDTK program cadres in 44 posyandu, spread across 13 sub-districts and 4 community health centers in Jambi City, with a total population of 220 cadres. The research sample was 51 cadres selected using a multistage sampling technique. Data collection was carried out using a questionnaire that had been tested for validity and reliability. Data analysis was carried out using univariate and bivariate tests using the chi-square test. Results: The results showed a significant relationship between motivation (p-value=0.005, PR 95% CI: 0.310 (0.124-0.774)), competence (p-value=0.006, PR 95% CI: 0.347 (0.154-0.783) ), communication skills (p-value=0.036, PR 95% CI: 2.080 (1.089-3.973)), and leadership (p-value=0.006, PR 95% CI: 2.400 (1.417-4.064)) with the effectiveness of posyandu cadres. Conclusion: There is a significant relationship between motivation, competence, communication skills and leadership and the effectiveness of posyandu cadres in implementing the SDIDTK Program in the Jambi City health center work area.